Discovery of boronic acid-based potent activators of tumor pyruvate kinase M2 and development of gastroretentive nanoformulation for oral dosing. (15th June 2021) - Patle, Rajkumar; Shinde, Shital; Patel, Sagarkumar; Maheshwari, Rahul; Jariyal, Heena; Srivastava, Akshay; Chauhan, Neelam; Globisch, Christoph; Jain, Alok; Tekade, Rakesh K.; Shard, Amit
Graphical abstract: Abstract: Several studies have established that cancer cells explicitly over-express the less active isoform of pyruvate kinase M2 (PKM2) is critical for tumorigenesis. The activation of PKM2 towards tetramer formation may increase affinity towards phosphoenolpyruvate (PEP) and avoidance of the Warburg effect. Herein, we describe the design, synthesis, and development of boronic acid-based molecules as activators of PKM2. The designed molecules were inspired by existing anticancer scaffolds and several fragments were assembled in the derivatives. 6a-6d were synthesized using a multi-step synthetic strategy in 55–70% yields, starting from cheap and readily available materials. The compounds were selectively cytotoxic to kill the cancerous cells at 80 nM, while they were non-toxic to the normal cells. The kinetic studies established the compounds as novel activators of PKM2 and ( E/Z )-(4-(3-(2-((4-chlorophenyl)amino)-4-(dimethylamino)thiazol-5-yl)-2-(ethoxycarbonyl)-3-oxoprop-1-en-1-yl) phenyl)boronic acid (6c) emerged as the most potent derivative. 6c was further evaluated using various in silico tools to understand the molecular mechanism of tetramer formation . Docking studies revealed that 6c binds to the PKM2 dimer at the dimeric interface. Further to ascertain the binding site and mechanism of action, rigorous MD (molecular dynamics) simulations were undertaken, which led to the conclusion that 6c stabilizes the center of the dimeric interface that possibly promotes tetramer formation. We further planned to make a tablet of the developed molecule for oral delivery, but it was seriously impeded owing to poor aqueous solubility of 6c . To improve aqueous solubility and retain 6c at the lower gastrointestinal tract, thiolated chitosan-based nanoparticles (TCNPs) were prepared and further developed as tablet dosage form to retain anticancer potency in the excised goat colon. Our findings may provide a valuable pharmacological mechanism for understanding metabolic underpinnings that may aid in the clinical development of new anticancer agents targeting PKM2.